European banking in transformational times: Regulation, crises, and challenges - Michael Koetter; Huyen Nguyen (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2023)
– This paper assesses the progress made towards the creation of the European Banking Union (EBU) and the evolution of the banking industry in the European Union since the financial crisis of 2007. We review major regulatory changes pertaining to the three pillars of the EBU and the effects of new legislation on both banks and the real economy. Whereas farreaching reforms pertaining to the EBU pillars of supervision and resolution regimes have been implemented, the absence of a European Deposit Scheme remains a crucial deficiency. We discuss how European banks coped with recent challenges, such as the Covid-19 pandemic, a high inflation environment, and digitalization needs, followed by an outlook on selected major challenges lying ahead of this incomplete EBU, notably the transition towards a green economy.
Keywords: 330